Optimization Model for Potable Water supply in Ladoke Akintola University of Technology Main Campus, Ogbomoso Oyo State, South-Western Nigeria - Ayodele A. ADEGBOLA; Elijah B. ADEWUMI; Olatunji S. OLANIYAN; Adebisi T. ADEYOKUNNU (UNIABUJA Journal of Engineering and Technology (UJET), 2025)
The demand for water supply in Ladoke Akintola University of Technology (LAUTECH), Ogbomoso is increasing due to population growth. In this study, an optimization model was developed to manage present and future demand for portable water supply in LAUTECH. A reconnaissance survey for water source was carried out from January to March 2018.Population of the students and staffs were obtained from Registry. Two hundred (200) questionnaires were distributed to various University staff to determine their water usage. The daily water demand from 2016 to 2046 was estimated using geometrical progression method. Yield of boreholes and wells were determined using recuperation method. New pipe network of the University was generated using Remote sensing data. Existing pipe networks in the University were used to determine Pipe discharge, velocity, pressure and diameter. Objective functions were formulated to optimize the pipe diameter and cost. There are twenty-two (22) boreholes in LAUTECH and only eleven (11) are functioning. The estimated total daily consumption for 2016 and 2046 were 1602.00 and 2043.40 m3/day, respectively. The yield of boreholes and wells were 1.331 l/s and 0.376 l/s, respectively. The estimated pipe discharge, velocity, pressure and diameter were 0.01 m3/s, 1.50 m/s, 1200 kN/m2 and 75 mm, respectively. Linear results produced 37 and 63% of 100 and 75mm diameter pipes respectively, equivalent to 16,389m pipe at a minimum cost of N54, 677, 450. The developed model can serve as baseline information for efficient water resources management in the University.